Induction and potential role of summer dormancy to enhance persistence of perennial grasses under warmer climates. (24th March 2022) - Shihan, Ammar; Barre, Philippe; Copani, Venera; Kallida, Rajae; Østrem, Liv; Testa, Giorgio; Norton, Mark R.; Sampoux, Jean‐Paul; Volaire, Florence
Abstract: The persistence of perennial herbaceous species is threatened by increasing aridity. However, summer dormancy is a strategy conferring superior survival to grasses adapted to hot and dry summers. The role of temperature on the induction of summer dormancy was investigated in the perennial grass Dactylis glomerata to analyse the potential expression of this strategy under warmer climates. We tested seven populations of D. glomerata originating from Morocco to Norway across the same latitudinal gradient in a five‐site experiment. One population of the highly summer‐dormant grass Poa bulbosa was used as a reference. Plants were grown from autumn in pots under full irrigation for 1 year mostly under open‐air shelters. Heading date (ear emergence preceding flowering) was recorded and foliage senescence was assessed from end of spring until autumn. The maximum plant senescence under summer irrigation indicated the level of dormancy expression. Summer dormancy onset, release, expression and duration were modelled as a function of climatic variables. From north to south, the duration of summer dormancy of the Mediterranean populations of D. glomerata and P. bulbosa ranged from 0 to 122 days, and 79 to 200 days, respectively. P. bulbosa was always completely dormant, while dormancy expression of D. glomerata was positively correlated with the sum of temperatures from winter onset ( R 2  = 0.57) and with the mean of minimum temperatures in summer ( R 2  = 0.73). Dormancy onset, release and duration were also positively correlated with thermal time from winter onset, while the duration of summer dormancy was longer as maximum temperatures increased. Mapping the European regions with climates allowing the expression of summer dormancy in D. glomerata showed that the potentially inductive areas for this strategy may expand in parallel with increasing summer aridity under a future climate warming scenario. Synthesis . The large phenotypic variability of the expression of summer dormancy in D. glomerata was driven by temperature, suggesting that this strategy may have a greater role in higher latitudes to increase plant survival over the predicted hotter and drier summers. Leveraging this strategy for the choice and selection of suitable populations could enhance future adaptation of major perennial grasses to climate change. Abstract : The maps show the past and future areas (brown) where summer dormancy can be expressed in the perennial grass Dactylis glomerata around the Mediterranean basin. The expression of summer dormancy in cocksfoot was driven by temperature, suggesting that this strategy may have a greater role in higher latitudes to increase plant survival over the predicted hotter and drier summers.